Visual Strategies for Eye and Head Movements During Table Tennis Rallies - Ryosuke Shinkai; Shintaro Ando; Yuki Nonaka; Tomohiro Kizuka; Seiji Ono (Frontiers Media S.A., 2022)
The purpose of this study was to clarify the properties of visual strategies for gaze, eye, and head movements in skilled table tennis players during rallies. Collegiate expert and semi-expert table tennis players conducted forehand rallies at a constant tempo using a metronome. Two tempo conditions were used in the order of 130 and 150 bpm. Participants conducted a 20-stroke rally under each tempo condition. Horizontal and vertical angles between the gaze point and ball positions at the time the ball bounced (gaze-ball angle) were analyzed with the image that was recorded by an eye tracking device equipped with Gyro sensor. Eye and head movements during rallies were also recorded with the eye tracking device and Gyro sensor, respectively. The results showed that the gaze-ball angle of expert players was significantly larger than that of semi-expert players. This result indicates that expert players tended to keep their gaze position on the ball shorter than semi-expert players. We also found that eye movements of expert players were significantly smaller than that of semi-expert players. Furthermore, as the result of multiple regression analysis, the effect of eye movements on the gaze-ball angle was significantly higher than that of head movements. This result indicates that the gaze-ball angle during table tennis rallies could be associated with eye movements rather than head movements. Our findings suggest that the visual strategies used during table tennis rallies are different between expert and semi-expert players, even though they both have more than 10 years of experience.